2010
DOI: 10.1088/0264-9381/27/4/045005
|View full text |Cite
|
Sign up to set email alerts
|

Teleparallel Lagrange geometry and a unified field theory

Abstract: Abstract. In this paper, we construct a field theory unifying gravity and electromagnetism in the context of Extended Absolute Parallelism (EAP-) geometry. This geometry combines, within its structure, the geometric richness of the tangent bundle and the mathematical simplicity of Absolute Parallelism (AP-) geometry. The constructed field theory is a generalization of the Generalized Field Theory (GFT) formulated by Mikhail and Wanas. The theory obtained is purely geometric. The horizontal (resp. vertical) fie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…We calculate the necessary components needed for Eq. (15). The non-vanishing components of N ab have the form 5…”
Section: Regularization Through Relocalization Of the Conserved Chargementioning
confidence: 99%
See 1 more Smart Citation
“…We calculate the necessary components needed for Eq. (15). The non-vanishing components of N ab have the form 5…”
Section: Regularization Through Relocalization Of the Conserved Chargementioning
confidence: 99%
“…The Poincaré gauge theory (PGT) is a gauge formulation of gravity which represents, at least at the classical level, a viable alternative to GR [15][16][17][18][19][20][21]. The investigation of the canonical structure of PGT has led to a significant improvement of our understanding of its gauge and physical properties [22].…”
Section: Introductionmentioning
confidence: 99%
“…Sub-Riemannian Geometry [1,4,10,15,16] has many applications such as diffusion, mechanics, gauge theories and control theory [7,13]. Absolute parallelism geometry or the geometry of parallelizable manifolds [3,17,20,21] is frequently used for applications in physics, especially in the geometrization of physical theories such general relativity and gravitation [6,12,14,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that many other scalars can be defined in AP-geometry and its different versions. These scalars have been used to construct several field theories with GR limits [13,28,30,34,35,36].…”
Section: Introductionmentioning
confidence: 99%